Enhanced power generation for total-cross-tied PV array using simulated annealing under partial shading conditions - Sai Krishna, Gundluru; Moger, Tukaram (IET renewable power generation, 2020)
Shade phenomena affect the PV module's power output, introduce multiple peak points in PV characteristics, and shorten the expected life cycle of the module. In order to prevent this issue, PV modules should reconfigure, namely, altering the electrical connections between PV modules based on the irradiance without changing their physical locations. As a result, the shading effects can distribute over the array and increase power output. This paper proposed a novel reconfiguration technique based on the simulated annealing algorithm to distribute shading impacts on 9$× $×9 total-cross-tied (TCT) PV array. In this work, the proposed algorithm produces a reconfigured connection matrix for 9$× $×9 TCT array that can minimize the current differences in each row and improve the power output. Various shading conditions have been taken to investigate the proposed technique by obtained global maximum power point (GMPP), current at GMPP, power loss, fill-factor, and efficiency. Further, the performance of the proposed technique is validated with other existing reconfiguration methods under partial shadings. In comparison with existing methods, the result shows that the proposed simulated annealing enhanced the power generation of the TCT array under all shading patterns.